PROPOSAL FOR THE DEVELOPMENT OF A WEB APPLICATION THAT ALLOWS TO MANAGE THE SCIENTIFIC CATEGORIES IN LACETEL - Barrios Martínez, Marité (Telemática, 2022)
The work describes the proposal for the development of a web application that allows to manage the scientific categories in LACETEL. Various tools and technologies are used, such as PHP programming language, using MySQL as a database manager, Apache as a web server, CodeIgniter as a development framework and NetBeans as a tool. In turn, the Model-View-Controller architectural pattern was used. The solution will allow each of the categorizable workers, and those who already have a scientific category, to prepare their scientific file. Both the file reviewers, as well as the managers at the different instances linked to the categorization process, will be able to observe the stage of the process, the levels of compliance or not by each worker in the preparation of the file, and take decision making in this regard. The solution, in addition, will alert workers about the times of fulfillment, delivery and activities to be carried out to opt for a scientific category.